Fatal Respiratory Diphtheria Caused by ß-Lactam–Resistant Corynebacterium diphtheriae. (9th August 2020) - Forde, Brian M; Henderson, Andrew; Playford, Elliott G; Looke, David; Henderson, Belinda C; Watson, Catherine; Steen, Jason A; Sidjabat, Hanna E; Laurie, Gordon; Muttaiyah, Sharmini; Nimmo, Graeme R; Lampe, Guy; et al.
Abstract: Background: Diphtheria is a potentially fatal respiratory disease caused by toxigenic Corynebacterium diphtheriae . Although resistance to erythromycin has been recognized, β-lactam resistance in toxigenic diphtheria has not been described. Here, we report a case of fatal respiratory diphtheria caused by toxigenic C. diphtheriae resistant to penicillin and all other β-lactam antibiotics, and describe a novel mechanism of inducible carbapenem resistance associated with the acquisition of a mobile resistance element. Methods: Long-read whole-genome sequencing was performed using Pacific Biosciences Single Molecule Real-Time sequencing to determine the genome sequence of C. diphtheriae BQ11 and the mechanism of β-lactam resistance. To investigate the phenotypic inducibility of meropenem resistance, short-read sequencing was performed using an Illumina NextSeq500 sequencer on the strain both with and without exposure to meropenem. Results: BQ11 demonstrated high-level resistance to penicillin (benzylpenicillin minimum inhibitory concentration [MIC] ≥ 256 μg/ml), β-lactam/β-lactamase inhibitors and cephalosporins (amoxicillin/clavulanic acid MIC ≥ 256 μg/mL; ceftriaxone MIC ≥ 8 μg/L). Genomic analysis of BQ11 identified acquisition of a novel transposon carrying the penicillin-binding protein (PBP) Pbp2c, responsible for resistance to penicillin and cephalosporins. When strain BQ11 was exposed to meropenem, selective pressure drove amplification of the transposon in a tandem array and led to a corresponding change from a low-level to a high-level meropenem-resistant phenotype. Conclusions: We have identified a novel mechanism of inducible antibiotic resistance whereby isolates that appear to be carbapenem susceptible on initial testing can develop in vivo resistance to carbapenems with repeated exposure. This phenomenon could have significant implications for the treatment of C. diphtheriae infection, and may lead to clinical failure. Abstract : This is the first reported case of β-lactam resistance in toxigenic Corynebacterium diphtheriae, which has a significant clinical impact, given there are rising rates of diphtheria worldwide, as well as broader implications from a public health perspective.